The Influence of the Work Environment and Individual Characteristics on Public Services at the Alim Village Office, Batang Cenaku District, Indragiri Hulu Regency - Ningsih, Fitria (International Journal of Applied Research and Sustainable Sciences, 2024)
The aim of this research is to determine the influence of the work environment and individual characteristics simultaneously on public services, to determine the influence of the work environment partially influencing public services and to determine individual characteristics partially influencing public services at the Alim Village Office, Batang Cenaku District, Indragiri Regency. Upstream. Using quantitative methods, the data analysis used is multiple linear analysis using the SPSS program. The sample in this research consisted of 89 respondents who had provided services at the Alim Village Office. This research was conducted from September 30 2022. The research results of the Work Environment and Individual Characteristics simultaneously influence Public Services, the Work Environment partially influences Public Services, Individual Characteristics partially influence Public Services.